Faktor yang Mempengaruhi Return Saham pada Perusahaan Asuransi yang Terdaftar di BEI - Rizky Ananda Ariza; Nur Ahmadi Bi Rahmani; Laylan Syafina (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research examines how PER, PBV, ROA, ROE, NPM, and DER influence stock returns in general insurance companies listed on the Indonesia Stock Exchange. This research also aims to test whether PER, PBV, ROA, ROE, NPM, and DER statistically influence stock returns in general insurance companies listed on the Indonesia Stock Exchange. This research uses quantitative methods. The population studied was five insurance companies registered on the IDX. A partial test using the t test shows that the Price Earning Ratio (PER) has no statistical effect on Stock Returns. Price Book Value (PBV) also has a small influence on stock returns. ROA and ROE have a statistically significant effect on stock returns. Stock returns are also influenced by Net Profit Margin (NPM). Lastly, the Debt Equity Ratio (DER) has no significant effect on stock returns. Simultaneous test (F Test) shows that Price Earning Ratio (PER), Price Book Value (PBV), Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Debt Equity Ratio (DER) collectively influence stock returns in insurance companies listed on the Indonesian Stock Exchange.